Efficacy of videoconferencing-delivered cognitive behavioural therapy to reduce anxiety disorder severity in LGBTQ+ people: An exploratory trial protocol - Isaac B. J. M. D. Dunn; Emma Power; Liam J. Casey; Bethany M. Wootton (PLoS ONE, 2025)
Objective Cognitive behavior therapy (CBT) is a well-established treatment for anxiety disorders in the general population. However, the efficacy of CBT for lesbian, gay, bisexual, transgender, queer, questioning, and otherwise non-heterosexual or non-cisgender (LGBTQ+) people with anxiety disorders is still emerging in the literature. This protocol proposes an exploratory, two-group, randomized controlled trial comparing the efficacy of CBT for anxiety disorders against a waitlist control group. Methods The trial will recruit 52 LGBTQ+ adults with a primary anxiety disorder diagnosis. The treatment will consist of videoconferencing-delivered CBT using the Unified Protocol (UP). The treatment will be provided in eight weekly individual sessions. Following treatment completion, the waitlist control participants will receive an LGBTQ+ adapted CBT intervention delivered via videoconferencing. The control group will receive the LGBTQ+ adapted UP in weekly sessions for eight weeks. Diagnostic status and symptom severity will be assessed at baseline, post-treatment, and three-month follow-up. Post-treatment qualitative exit interviews will collect participant perspectives on treatment acceptability. Results Outcome measures will be compared across groups and benchmarked with existing literature to assess efficacy and feasibility, while qualitative analysis will explore intervention acceptability. Conclusion The results are anticipated to inform best-practice remote transdiagnostic treatment of anxiety disorders in LGBTQ+ people.